Oxytocin for labour induction or augmentation as a risk factor for autism: systematic literature review - Marija Grosek; Miha Lučovnik (Nurses and Midwives Association of Slovenia, 2017)
Introduction: Some studies have shown a potential association between oxytocin use during labour and autism spectrum disorder in children (ASD). We performed a systematic review of recent studies examining this association. Methods: Boolean operators (AND/OR) were used to search MEDLINE using the following search criteria: Autistic Disorder or Autism Spectrum Disorder or Autism and Labour Induction or Labour Augmentation. Articles published in English in 2013 or later were considered. Additional studies were identified by reviewing citations. Only studies conducted on people were included. Studies not accounting for potential confounding factors were excluded. Results: Four retrospective cohort studies met the inclusion criteria. One showed an association between labour induction and augmentation and ASD, one showed a weak association between labour augmentation in boys and ASD, and one showed no association between labour induction or augmentation and ASD. The largest study showed a weak association between labour induction and ASD, which was not significant when siblings were analyzed separately. Discussion and conclusions: Recently published studies do not support the hypothesis of a causal relationship between oxytocin use during labour and ASD. Benefits of medically indicated induction or augmentation of labour outweigh the theoretical risk of ASD.